BULGARIAN LITERATURE AND CHRISTIANITY: THE BIG QUESTION OF A “SMALL” NATION - Ewelina DRZEWIECKA (Езиков свят)
The paper raises the question of the relationship between the Christian religion and Bulgarian literature as it is regarded as one of the “big questions” in modern Bulgarian culture. This article takes / assumes as its starting point an established belief, one that has been repeatedly discredited, that Bulgarian literature is “quite poor in terms of philosophical and moral-religious motives” (Boyan Penev). The notion of “small nation,” which is a reference to a famous concept by Miroslav Hroch, serves as a call to reconsider traditionally accepted classifications and taxonomies in specific perspectives related to the cultural history of Bulgarian humanities, as well as the history of ideas. The cultural phenomenon “Christianity in / of Bulgarian literature” is addressed within the context of the modern “grand narrative” which encompasses matters of religion in relation to modernity. The analysis draws on and references the famous thesis by Talas Asad on the so-called “Protestant bias” within the modern humanities and social sciences. The prejudice of (non-)religious Bulgarians (respectively Bulgarian literature) is commented within the epistemological horizon given by the postsecular thought which claims that the “religious-secular” opposition is discursive and contextual, and the academic discourse is entangled with various cryptotheologies. The analysis aims to show that deconstructing notions and meanings that have been imposed in research of European “periphery” (“a small nation”) may shatter the established “truths” about modernity and its relationship to religion and “secular” idea(l)s. It is suggested that nowadays, Bulgarian studies have great potential because they can contribute to current critical attempts to penetrate, undermine and dismantle from within the dominant systems of understanding and classifying “(non-)religious” phenomena.